Tuning Phase Structure of Nickel–Ruthenium Alloys via MOFs In Situ Hydrolysis toward Enhanced Hydrogen Evolution Performance in Alkaline. Issue 2 (22nd December 2021) - Meng, Tian; Chen, Yuting; Xing, Zhicai; Yang, Xiurong
Abstract: Metal organic frameworks (MOFs) and corresponding derivatives have attracted wide attention. As electrocatalysts, these derivatives (metal, metal compound, and associated composites) have a wide range of application in water‐splitting devices, fuel cells, and other hydrogen‐related technologies. However, with the exception of pyrolysis, limited studies have documented generated metal nanoparticles from MOFs hydrolysis reactions. Herein, NiRu dual‐phase alloy nanoparticles are synthesized via in situ MOFs hydrolysis mediating solvothermal reduction reaction. The hcp ‐phase NiRu alloys can be rationally tuned by modulating experimental parameters of feeding metal ratio and reaction time. The volcanic link between hydrogen evolution reaction activity and the descriptor of d band center is investigated using experimentally determined valence bands. Furthermore, compared with fcc ‐phase NiRu alloys, it is theoretically revealed that hcp ‐phase NiRu alloys optimize d band structure and have a lower energy barrier. This finding broadens the range of application for MOFs hydrolysis reactions and highlights advantages of metal alloys manufactured from MOFs hydrolysis reactions. Abstract : Nickel‐ruthenium dual‐phase alloys (NiRuDPA) are first synthesized by in situ metal organic framework hydrolysis mediating solvothermal reduction reactions. NiRuDPA with hcp ‐phase exhibit superior d band structure and lower theoretical thermodynamic energy barrier of hydrogen evolution reaction (HER). The obtained Ni0.90 Ru0.10 DPA electrocatalyst exhibits very fine HER performance closed to that of commercial platinum/carbon in alkaline media.